Technical note: Sources of systemic error in total body irradiation and total skin electron therapy in vivo measurements using nanoDot optically stimulated luminescence dosimeters within high‐efficiency clinics. Issue 5 (4th March 2022) - Yoon, Suk Whan; Lin, Hui; Mihailidis, Dimitris; Kennedy, Christopher; Li, Taoran
Abstract: Purpose: To identify sources of systemic errors and estimate their effects, especially the vendor‐provided sensitivity Ss, i, vendor, on total body irradiation (TBI) and total skin electron therapy (TSET) in vivo OSLD measurements. Materials: Calibration nanoDot OSLDs were irradiated 50–300cGy under reference conditions. Raw OSLD readings M raw were corrected by Ss, i, vendor to obtain corrected readings M corr . A quadratic calibration curve relating M corr to delivered dose D w was established and commissioned for clinical use. For clinical measurements, directly adjacent pairs of nanoDot OSLDs were placed on TBI and TSET patients with a medical tape with or without 1.5 cm of bolus respectively before treatment. Used OSLDs were bleached between each use until cumulative dose of 15 Gy. Relative difference in corrected counts (∆ M corr, rel  = pair‐difference/mean) was fitted multi‐linearly versus possible sources of systemic errors ( Ss, i, vendor, bleaching history, cumulative dose, and age differences). Total of 101 TBI and 110 TSET measurement pairs from calibrated batches were analyzed. Results: Ss, i, vendor introduced a residual systemic error to corrected readings M corr (−0.98% per +0.01, p  = 4e−12). Given Ss, i, vendor distribution is σ = ±0.025, measured dose 1−σ error is ±2.5%, compared to ±2.8% uncertainty reported in the literature which may include this systemic error. Bleaching or cumulative dose did not affect M corr significantly after adjusting for Ss, i, vendor . Adjusting for the systemic error in Ss, i, vendor decreased two‐sample mean D w median absolute error from ±2.6% to ±1.9% and 95‐percentile absolute error from ±7.1% to ±5.5%. Variability between paired clinical OSLDs was larger for TBI versus TSET at σpd  = ±4.7% and ±6.3%, respectively, despite similar predictor distributions. Conclusion: Our findings suggest that M raw correction via vendor‐provided sensitivity results in a small but significant systemic error. Dosimeters with outlier sensitivities should be excluded during batch calibration to minimize error. Bleaching and cumulative dose likely minimally affect measurements if cumulative dose is controlled below 15 Gy. Random errors were higher for TSET than TBI.